2018
DOI: 10.1007/s11079-018-9503-2
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing and Analysing the Determinants of Current Accounts’ Cyclicality: Evidence from the Euro Area

Abstract: In this paper, we decompose the current account (CA) balance in 19 Euro area countries into cyclical and non-cyclical components. For the period 1999:Q1 to 2015:Q4, we compute income elasticities of imports and of exports via an alternative novel and improved approach by running time-varying coefficient models country-by-country. Then, in a panel set-up (and controlling for country-invariant characteristics), we uncover that terms of trade have a positive effect on both the cyclical and noncyclical components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The empirical strategy is based on the Phillips et al ( 2013 ) model, which is used by Afonso and Jalles ( 2019 ) and Mohanty ( 2019 ) to establish the link between fiscal policy and external balance, and specifically produces the equation as: …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The empirical strategy is based on the Phillips et al ( 2013 ) model, which is used by Afonso and Jalles ( 2019 ) and Mohanty ( 2019 ) to establish the link between fiscal policy and external balance, and specifically produces the equation as: …”
Section: Methodsmentioning
confidence: 99%
“…The analysis quantifies the impact of the real effective exchange rate, predicted real growth, and terms of trade in explaining the current account balance. In recent research, Afonso and Jalles ( 2019 ) seek to dissect the current account balance into cyclical and non-cyclical components. In a study of 19 Euro area countries, these authors uncover the negative effects of terms of trade on both components, while showing that employee wages, level of employment, and global financial crises have a negative impact on only the cyclical component.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Riaz, Javid, and Mubarik (2019) investigated this issue for South Asian Economies and concluded that domestic income and foreign assets play a crucial role in this regard. Afonso and Jalles (2019) focused on investigating the determinants of variation in CAB in nineteen Euro countries. They, first, divided the whole sample into two broader categories, cyclical-sample, and non-cyclical sample, and second, they calculated the exports-elasticities and import-elasticities with respect to income for each country one by one.…”
Section: Graph 1: Cad As % Of Gdpmentioning
confidence: 99%
“…In this regard, Carrasco (2018) concludes that countries such as Belgium, Germany, Luxembourg, and the Netherlands have structural external surpluses, whereas Greece, Portugal and Spain have structural external deficits. Afonso and Jalles (2018) report a negative effect of the Global Financial Crisis on the cyclical component of the current account for Italy, Ireland, Portugal, Spain, and Latvia. As of 2010, with the sovereign debt crisis in Greece and the subsequent contagion to other peripheral economies (see Lane, 2012), the external imbalances verified in some Eurozone countries faded, especially in deficit countries.…”
Section: Introductionmentioning
confidence: 99%